Method for producing inorganic material
By pulverizing the sulfide-based solid electrolyte material in an all-solid lithium-ion battery using a ball mill and recovering the material through a separation device, the problem of insufficient battery energy density is solved, and the preparation of small-particle-sized materials and the inhibition of aggregates is achieved.
Patent Information
- Application Number
- CN202180069809.8
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Priority Date
- 2020-10-15
- Filing Date
- 2021-10-08
- Publication Date
- 2025-04-08
- Estimated Expiration
- 2041-10-08
AI Technical Summary
In all-solid lithium-ion batteries, the proportion of sulfide-based solid electrolyte materials in the electrode active material layer or the thickness of the solid electrolyte layer is difficult to reduce, resulting in insufficient energy density.
By pulverizing the first inorganic material using a ball mill composed of a cylindrical container and a crushing ball, a second inorganic material with a small average particle size is obtained, and the second inorganic material is recovered from the crushing ball by a separation device to inhibit the formation of the condensed ball.
Inorganic materials with small average particle size are achieved, the formation of condensed materials is suppressed, and the inorganic materials attached to the crushing balls are recovered, thereby increasing the energy density of the battery.
Smart Images

Figure CN116490285B_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to a method for producing an inorganic material. Background Art
[0002] Lithium-ion batteries are generally used as power sources for small portable devices such as mobile phones and notebook computers. In addition, lithium-ion batteries have recently begun to be used as power sources for electric vehicles, power storage, and the like in addition to small portable devices.
[0003] Currently commercially available lithium-ion batteries use electrolytes containing flammable organic solvents. On the other hand, lithium-ion batteries that are fully solid by replacing the electrolyte with a solid electrolyte (hereinafter also referred to as all-solid-state lithium-ion batteries) do not use flammable organic solvents in the battery, so it is believed that safety devices can be simplified, and manufacturing costs and productivity are excellent.
[0004] As a solid electrolyte material used for such a solid electrolyte, for example, a sulfide-based solid electrolyte material is known.
[0005] For example, Patent Document 1 (Japanese Patent Application Laid-Open No. 2016-27545) describes a sulfide-based solid electrolyte material characterized by having a peak at 2θ=29.86°±1.00° in X-ray diffraction measurement using CuKα rays and having Li 2y+3 The composition of PS4 (0.1≤y≤0.175).
[0006] Prior art literature
[0007] Patent Literature
[0008] Patent document 1: Japanese Patent Application Publication No. 2016-27545. Summary of the invention
[0009] Problem that the invention aims to solve
[0010] The increase in energy density of all-solid-state lithium-ion batteries can be achieved, for example, by reducing the proportion of the solid electrolyte material in the electrode active material layer or reducing the thickness of the solid electrolyte layer provided between the positive electrode and the negative electrode.
[0011] Here, in order to reduce the proportion of the solid electrolyte material in the electrode active material layer or reduce the thickness of the solid electrolyte layer, the average particle size of the solid electrolyte material is preferably small.
[0012] According to the research conducted by the present inventors, it has been found that the sulfide-based inorganic solid electrolyte material described in Patent Document 1 is soft due to the presence of sulfur, and when pulverized vigorously, it may aggregate and become fixed to the inner wall of a cylindrical container.
[0013] The present invention has been made in view of the above circumstances, and provides a method for producing an inorganic material capable of suppressing the generation of aggregates and obtaining an inorganic material having a small average particle size.
[0014] Means used to solve problems
[0015] One embodiment of the present invention is a method for producing an inorganic material, comprising:
[0016] A step (A) of preparing a first inorganic material as a raw material;
[0017] A step (B) of obtaining a second inorganic material by pulverizing the first inorganic material using a ball mill composed of a cylindrical container and pulverizing balls to micronize the first inorganic material; and
[0018] a step (C) of separating the second inorganic material from the crushing balls to which the second inorganic material is attached,
[0019] The process (B) includes: after placing the first inorganic material and the crushing balls in the cylindrical container, a process (B1) of rotating the cylindrical container around the cylindrical axis; and a process (B2) of moving the cylindrical container so that the first inorganic material moves along the cylindrical axis.
[0020] Effects of the Invention
[0021] According to the above aspect of the present invention, it is possible to provide a method for producing an inorganic material that can suppress the generation of aggregates and obtain an inorganic material having a small average particle size. BRIEF DESCRIPTION OF THE DRAWINGS
[0022] Figure 1 It is a schematic diagram for explaining the movement of the ball mill in Examples 1 and 2 and the comparative example, Figure 1 (a) is Examples 1 to 2, Figure 1 (b) is a comparative example.
[0023] Figure 2 It is a schematic plan view of a separation device used in step (C) of the method for producing an inorganic material according to the first embodiment.
[0024] Figure 3 is along Figure 2 Schematic cross-sectional view of AA′.
[0025] Figure 4 This is an enlarged schematic diagram of a part of the mesh member of Embodiment 1.
[0026] Figure 5 It is a schematic top view of the separation device of Embodiment 2.
[0027] Figure 6 It is a side schematic diagram of the separation device of embodiment 2.
[0028] Figure 7 is along Figure 5 Schematic cross-sectional view of BB′.
[0029] Figure 8 This is an enlarged schematic diagram of a part of the mesh member of the second embodiment.
[0030] Fig. 9 It is a schematic diagram of a separation device according to a modified example.
[0031] Fig.10 This is a diagram showing a SEM image of the second inorganic material separated from the pulverizing balls in Example 1.
[0032] Fig.11 This is a diagram showing a SEM image of the second inorganic material separated from the pulverizing balls in Example 2. DETAILED DESCRIPTION
[0033] The following is an explanation of the embodiments of the present invention using the accompanying drawings. It should be noted that in all the drawings, the same components are marked with the same reference numerals, and the description is appropriately omitted. Unless otherwise specified, the numerical range "A to B" means greater than A and less than B.
[0034] (Implementation Method 1)
[0035] The manufacturing method of the inorganic material of embodiment 1 includes: a step (A) of preparing a first inorganic material to be a raw material; a step (B) of obtaining a second inorganic material by crushing the first inorganic material using a ball mill composed of a cylindrical container and crushing balls to micronize the first inorganic material; and a step (C) of separating the second inorganic material from the crushing balls to which the second inorganic material is attached, wherein the step (B) includes: after placing the first inorganic material and the crushing balls in the cylindrical container, rotating the cylindrical container about the cylindrical axis (B1); and a step (B2) of moving the cylindrical container so that the first inorganic material moves along the cylindrical axis.
[0036] According to the method for producing an inorganic material of this embodiment, the generation of aggregates can be suppressed and an inorganic material with a small average particle size can be obtained. In addition, the second inorganic material can be attached to the crushing balls compared to the inner wall of the cylindrical container, and the second inorganic material attached to the crushing balls can be recovered.
[0037] Next, each step will be described in detail.
[0038] (Process (A))
[0039] First, a first inorganic material is prepared as a raw material. The first inorganic material may be manufactured or purchased from a commercial product.
[0040] The first inorganic material is not particularly limited as long as it is a material that is required to be micronized, and examples thereof include inorganic solid electrolyte materials, positive electrode active materials, negative electrode active materials, and the like.
[0041] The inorganic solid electrolyte material is not particularly limited, and examples thereof include sulfide-based inorganic solid electrolyte materials, oxide-based inorganic solid electrolyte materials, and other lithium-based inorganic solid electrolyte materials. Among them, sulfide-based inorganic solid electrolyte materials are preferred.
[0042] The inorganic solid electrolyte material is not particularly limited, and examples thereof include materials used to constitute a solid electrolyte layer of an all-solid-state lithium ion battery.
[0043] As sulfide-based inorganic solid electrolyte materials, for example, there can be cited Li2S-P2S5 materials, Li2S-SiS2 materials, Li2S-GeS2 materials, Li2S-Al2S3 materials, Li2S-SiS2-Li3PO4 materials, Li2S-P2S5-GeS2 materials, Li2S-Li2O-P2S5-SiS2 materials, Li2S-GeS2-P2S5-SiS2 materials, Li2S-SnS2-P2S5-SiS2 materials, Li2S-P2S5-Li3N materials, Li2S 2+X -P4S3 materials, Li2S-P2S5-P4S3 materials, etc.
[0044] Among them, Li2S-P2S5 materials and Li2S-P2S5-Li3N materials are preferred from the perspective of excellent lithium ion conductivity and stability that does not cause decomposition in a wide voltage range. Here, for example, Li2S-P2S5 material refers to an inorganic material obtained by chemically reacting an inorganic composition containing at least Li2S (lithium sulfide) and P2S5 with each other through mechanical treatment, and Li2S-P2S5-Li3N material refers to an inorganic material obtained by chemically reacting an inorganic composition containing at least Li2S (lithium sulfide), P2S5 and Li3N with each other through mechanical treatment.
[0045] Here, in the present embodiment, lithium sulfide also includes lithium polysulfide.
[0046] As the above-mentioned oxide-based inorganic solid electrolyte material, for example, NASICON type such as LiTi2(PO4)3, LiZr2(PO4)3, LiGe2(PO4)3 can be cited; (La 0.5+x Li 0.5-3x)TiO3 and other perovskite types; Li2O-P2O5 materials, Li2O-P2O5-Li3N materials, etc.
[0047] As other lithium-based inorganic solid electrolyte materials, for example, LiPON, LiNbO3, LiTaO3, Li3PO4, LiPO 4-x N x (x is 0<x≤1), LiN, LiI, LISICON, etc.
[0048] Furthermore, glass ceramics obtained by precipitating crystals of these inorganic solid electrolytes can also be used as an inorganic solid electrolyte material.
[0049] The sulfide-based inorganic solid electrolyte material of the present embodiment preferably contains as constituent elements Li, P, and S. In addition, for the sulfide-based inorganic solid electrolyte material of the present embodiment, the sulfide-based inorganic solid electrolyte material as the first inorganic material is preferably in a glass state from the viewpoint of being able to obtain a further smaller average particle size.
[0050] In addition, for the sulfide-based inorganic solid electrolyte material of the present embodiment, from the viewpoint of further improving lithium ion conductivity, electrochemical stability, stability in water or air, and handleability, the molar ratio of the Li content to the P content (Li / P) in the solid electrolyte material is preferably 1.0 to 10.0, more preferably 2.0 to 5.0, further preferably 2.5 to 4.0, further preferably 2.8 to 3.6, further preferably 3.0 to 3.5, further preferably 3.1 to 3.4, and particularly preferably 3.1 to 3.3. In addition, the molar ratio of the S content to the P content (S / P) is preferably 1.0 to 10.0, more preferably 2.0 to 6.0, further preferably 3.0 to 5.0, further preferably 3.5 to 4.5, further preferably 3.8 to 4.2, further preferably 3.9 to 4.1, and particularly preferably 4.0.
[0051] Here, the contents of Li, P, and S in the solid electrolyte material of the present embodiment can be determined by, for example, ICP emission spectrometry or X-ray photoelectron spectroscopy.
[0052] The sulfide-based inorganic solid electrolyte material of the present embodiment can be used for any purpose requiring lithium ion conductivity. Among them, the sulfide-based inorganic solid electrolyte material of the present embodiment is preferably used for lithium ion batteries. More specifically, it is used for the positive electrode active material layer, the negative electrode active material layer, the electrolyte layer, etc. in the lithium ion battery. Furthermore, the sulfide-based inorganic solid electrolyte material of the present embodiment is suitable for constituting the positive electrode active material layer, the negative electrode active material layer, the solid electrolyte layer, etc. of an all-solid-state lithium ion battery, and is particularly suitable for constituting the solid electrolyte layer of an all-solid-state lithium ion battery.
[0053] An example of an all-solid-state lithium-ion battery to which the sulfide-based inorganic solid electrolyte material of the present embodiment is applied is a battery in which a positive electrode, a solid electrolyte layer, and a negative electrode are stacked in this order.
[0054] The positive electrode active material is not particularly limited, and examples thereof include positive electrode active materials that can be used for the positive electrode layer of a lithium ion battery. Examples thereof include lithium cobalt oxide (LiCoO2), lithium nickel oxide (LiNiO2), lithium manganese oxide (LiMn2O4), solid solution oxide (Li2MnO3-LiMO2 (M=Co, Ni, etc.)), lithium-manganese-nickel oxide (LiNi 1 / 3 Mn 1 / 3 Co 1 / 3O2), olivine-type lithium phosphorus oxide (LiFePO4) and other composite oxides; CuS, Li-Cu-S compounds, TiS2, FeS, MoS2, V2S5, Li-Mo-S compounds, Li-Ti-S compounds, Li-VS compounds, Li-Fe-S compounds and other sulfide-based positive electrode active materials, etc.
[0055] The negative electrode active material is not particularly limited, and examples thereof include negative electrode active materials that can be used for the negative electrode layer of a lithium ion battery. For example, metal-based materials mainly composed of lithium alloys, tin alloys, silicon alloys, gallium alloys, indium alloys, and aluminum alloys; lithium-titanium composite oxides (e.g., Li4Ti5O 12 ); graphite materials, etc.
[0056] Next, a method for producing a glassy sulfide-based inorganic solid electrolyte material will be described.
[0057] For example, a mixture containing lithium sulfide and phosphorus sulfide is prepared, and then the mixture is mechanically treated to chemically react and vitrify the lithium sulfide and phosphorus sulfide as raw materials, thereby obtaining a glassy sulfide-based inorganic solid electrolyte material.
[0058] The mixture containing lithium sulfide and phosphorus sulfide can be obtained, for example, by mixing the respective raw materials at a predetermined molar ratio so that the target sulfide-based inorganic solid electrolyte material has a desired composition ratio.
[0059] Here, the mixing ratio of each raw material in the mixture is adjusted so that the obtained sulfide-based inorganic solid electrolyte material has a desired composition ratio.
[0060] The method for mixing the raw materials is not particularly limited as long as it is a mixing method that can uniformly mix the raw materials. For example, mixing can be performed using a ball mill, a bead mill, a vibration mill, a percussion pulverizer, a mixer (a pug mixer, a ribbon mixer, a tumble mixer, a cylindrical mixer, a V-type mixer, etc.), a kneader, a double-shaft kneader, an air flow mill, etc.
[0061] Mixing conditions such as stirring speed, treatment time, temperature, reaction pressure, and gravitational acceleration applied to the mixture when mixing the raw materials can be appropriately determined according to the amount of the mixture to be treated.
[0062] The lithium sulfide used as a raw material is not particularly limited, and commercially available lithium sulfide can be used, or lithium sulfide obtained by, for example, reacting lithium hydroxide with hydrogen sulfide can be used. From the viewpoint of obtaining a high-purity sulfide-based inorganic solid electrolyte material and suppressing side reactions, it is preferred to use lithium sulfide with less impurities.
[0063] Here, in this embodiment, lithium sulfide also includes lithium polysulfide. As lithium sulfide, Li2S is preferred.
[0064] There are no particular limitations on the phosphorus sulfide used as a raw material, and commercially available phosphorus sulfide (e.g., P2S5, P4S3, P4S7, P4S5, etc.) can be used. From the perspective of obtaining a high-purity sulfide-based inorganic solid electrolyte material and suppressing side reactions, it is preferred to use phosphorus sulfide with few impurities. As the phosphorus sulfide, P2S5 is preferred.
[0065] As a raw material, lithium nitride can also be used. Here, nitrogen in lithium nitride is discharged into the system in the form of N2, so by using lithium nitride as a raw material, it is possible to increase only the Li composition relative to the sulfide-based inorganic solid electrolyte material containing Li, P and S as constituent elements.
[0066] The lithium nitride of this embodiment is not particularly limited, and commercially available lithium nitride (such as Li3N, etc.) can be used, or lithium nitride obtained by, for example, reacting metallic lithium (such as Li foil) and nitrogen can be used. From the perspective of obtaining a high-purity solid electrolyte material and suppressing side reactions, it is preferred to use lithium nitride with few impurities.
[0067] Then, the mixture containing lithium sulfide and phosphorus sulfide is mechanically treated to chemically react and vitrify the lithium sulfide and phosphorus sulfide as raw materials, thereby obtaining a glassy sulfide-based inorganic solid electrolyte material.
[0068] Here, the mechanical treatment is a treatment that can cause a chemical reaction and vitrification by causing two or more inorganic compounds to mechanically collide with each other, and examples thereof include mechanochemical treatment.
[0069] In the vitrification step, from the viewpoint of easily achieving an environment in which moisture and oxygen are removed at a high level, the mechanical treatment is preferably performed in a dry manner, and dry mechanochemical treatment is more preferred.
[0070] When mechanochemical treatment is used, each raw material can be mixed while being crushed into fine particles, thereby increasing the contact area of each raw material, thereby promoting the reaction of each raw material, and thus, a glassy sulfide-based inorganic solid electrolyte material can be obtained more efficiently.
[0071] Here, mechanochemical treatment refers to a method of vitrifying the composition as an object while applying mechanical energy such as shear force, impact force or centrifugal force. As a device for vitrification by mechanochemical treatment, there can be cited crushing / dispersing machines such as ball mills, bead mills, vibration mills, turbine grinders, mechanical fusion machines, disc mills, and roller mills; rotating / impact crushing devices composed of a mechanism combining rotation (shear stress) and impact (compression stress) represented by rock drills, vibration drills, impact drivers, etc.; high-pressure grinding rollers, etc. Among them, from the viewpoint of being able to efficiently generate very high impact energy, ball mills and bead mills are preferred, and ball mills are particularly preferred. In addition, from the viewpoint of excellent continuous productivity, it is preferred to be: a roller mill; a rotating / impact crushing device composed of a mechanism combining rotation (shear stress) and impact (compression stress) represented by rock drills, vibration drills, impact drivers, etc.; high-pressure grinding rollers, etc.
[0072] In addition, the mechanochemical treatment is preferably performed under an inactive environment, thereby suppressing the reaction of the sulfide-based inorganic solid electrolyte material with water vapor, oxygen, and the like.
[0073] In addition, the above-mentioned inert environment refers to a vacuum environment or an inert gas environment. In the above-mentioned inert environment, in order to avoid moisture contact, the dew point is preferably below -30°C, more preferably below -50°C, and particularly preferably below -60°C. The above-mentioned inert gas environment refers to an environment of inert gases such as argon, helium, and nitrogen. In order to avoid impurities from being mixed into the product, the higher the purity of these inert gases, the more preferred. As a method for introducing an inert gas into a mixed system, there is no particular limitation as long as the mixed system is filled with an inert gas environment, and examples include a method of purging the inert gas, a method of continuously introducing a specified amount of inert gas, and the like.
[0074] When the mixture containing lithium sulfide and phosphorus sulfide is mechanically treated, the mixing conditions such as the rotation speed, treatment time, temperature, reaction pressure, and gravitational acceleration applied to the mixture can be appropriately determined according to the type of the mixture and the amount of treatment. Generally, the faster the rotation speed, the faster the glass formation speed, and the longer the treatment time, the higher the conversion rate to glass.
[0075] Generally, when X-ray diffraction analysis is performed using CuKα rays as a radiation source, when the diffraction peak derived from the raw material disappears or decreases, it can be determined that the mixture is vitrified and a glassy sulfide-based inorganic solid electrolyte material is obtained.
[0076] Here, in the step of vitrifying the mixture containing lithium sulfide and phosphorus sulfide, it is preferred to perform mechanical treatment until the lithium ion conductivity is 0.5×10 -4 S cm -1 Above, preferably 1.0×10 -4 S cm -1 As described above, a sulfide-based inorganic solid electrolyte material having even better lithium ion conductivity can be obtained.
[0077] (Process (B))
[0078] Then, with the following Figure 1 In the example shown in (a), the first inorganic material prepared in step (A) is pulverized using a ball mill composed of a cylindrical container and pulverizing balls to obtain a second inorganic material by micronizing the first inorganic material.
[0079] Step (B) includes: after placing the first inorganic material and crushing balls in a cylindrical container, a step (B1) of rotating the cylindrical container about the cylindrical axis; and a step (B2) of moving the cylindrical container so that the first inorganic material moves along the cylindrical axis.
[0080] Here, step (B1) and step (B2) may be performed simultaneously or separately. In addition, step (B2) may be performed continuously or intermittently while step (B1) is being performed.
[0081] Preferably, the first inorganic material is pulverized in a dry state in step (B). When pulverized in a dry state, an organic solvent or water as a dispersion medium is not required, and deterioration caused by reaction and hydrolysis of the inorganic material and organic molecules can be prevented. Furthermore, the step of separating the organic solvent and water is not required, and the manufacturing process can be simplified.
[0082] Here, in the present embodiment, the ball mill composed of a cylindrical container and grinding balls is a ball mill that rotates about the cylindrical axis, and does not include a planetary motion type ball mill.
[0083] In addition, step (B) is preferably performed under an inert environment, thereby suppressing the reaction of the inorganic material with water vapor, oxygen, and the like.
[0084] In addition, the above-mentioned inert environment refers to a vacuum environment or an inert gas environment. In the above-mentioned inert environment, in order to avoid moisture contact, the dew point is preferably below -30°C, more preferably below -50°C, and particularly preferably below -60°C. The above-mentioned inert gas environment refers to an environment of inert gases such as argon, helium, and nitrogen. In order to avoid impurities from being mixed into the product, the higher the purity of these inert gases, the more preferred. As a method for introducing an inert gas into a mixed system, there is no particular limitation as long as the mixed system is filled with an inert gas environment, and examples include a method of purging the inert gas, a method of continuously introducing a specified amount of inert gas, and the like.
[0085] The pulverization conditions in step (B), such as the treatment time, temperature, and gravitational acceleration applied to the inorganic material, can be appropriately determined according to the type and treatment amount of the inorganic material.
[0086] The rotation speed of the cylindrical container in step (B1) can be appropriately determined according to the type and treatment amount of the inorganic material and is therefore not particularly limited, but is, for example, 30 rpm to 200 rpm, preferably 60 rpm to 120 rpm.
[0087] In addition, the rotation speed of the cylindrical container is preferably equal to or lower than the critical rotation speed.
[0088] The critical speed is the speed at which the grinding balls rotate in close contact with the inner wall of the cylindrical container when the centrifugal force and gravity of the grinding balls are balanced. When the diameter of the grinding balls is negligible compared to the inner diameter D [m] of the cylindrical container, the critical speed (Nc) is expressed as Nc [rpm] = 42.3 / √D.
[0089] In the method for manufacturing inorganic materials of the present embodiment, in step (B2), for example, the inorganic material can be moved along the cylindrical axis direction by causing the cylindrical container to reciprocate along the cylindrical axis direction and / or causing at least one end of the cylindrical container to reciprocate in a direction perpendicular to the cylindrical axis direction.
[0090] The speed of the reciprocating motion in step (B2) can be appropriately determined according to the type and treatment amount of the inorganic material and is therefore not particularly limited, but is, for example, 1 cpm to 30 cpm, preferably 2 cpm to 6 cpm.
[0091] The diameter of the grinding balls is, for example, 0.1 mm or more and 10.0 mm or less, and is preferably 1.0 mm or more and 3.0 mm or less from the viewpoint of obtaining a further smaller average particle diameter.
[0092] In the method for producing an inorganic material of the present embodiment, the grinding balls preferably include two or more grinding balls having different diameters, and more preferably include three or more grinding balls having different diameters. This can produce an inorganic material with a smaller average particle size.
[0093] In addition, in the method for producing an inorganic material of the present embodiment, the crushing balls preferably include a first crushing ball having a diameter in the range of 1.5 mm to 2.5 mm and a second crushing ball having a diameter in the range of 0.2 mm to less than 1.5 mm, and more preferably, in addition to the first crushing ball and the second crushing ball, a third crushing ball having a diameter in the range of greater than 2.5 mm to 10.0 mm is included. Thus, an inorganic material having a smaller average particle size can be obtained.
[0094] Preferably, at least the surface of the pulverizing ball is made of at least one material selected from ceramic materials and metal materials.
[0095] Examples of the metal material include centrifugally hardened steel, SUS, Cr-plated SUS, Cr-plated hardened steel, and the like.
[0096] Furthermore, when at least the surface of the pulverizing ball of the present embodiment is made of a ceramic material, it is possible to suppress mixing of unnecessary metal components from the pulverizing ball into the obtained inorganic material, and thus it is possible to obtain an inorganic material with a higher purity.
[0097] Examples of such ceramic materials include stabilized zirconia, alumina, silicon carbide, silicon nitride, and the like.
[0098] In the manufacturing method of the inorganic material of the present embodiment, as required, before step (B), a step of classifying the first inorganic material can also be performed. By removing coarse particles from the first inorganic material through the classification operation, the first inorganic material can be further effectively micronized in step (B). There is no particular limitation on the classification method, and a known method such as a sieve can be used.
[0099] The second inorganic material obtained by the method for producing an inorganic material according to the present embodiment is not particularly limited, and the average particle size d in the weight-based particle size distribution according to the laser diffraction scattering particle size distribution measurement method is 1: 50 It is preferably 0.01 μm to 20 μm, more preferably 0.05 μm to 10 μm, further preferably 0.10 μm to 8.0 μm, further preferably 0.10 μm to 5.0 μm, further preferably 0.50 μm to 4.0 μm.
[0100] By adjusting the average particle size d of the second inorganic material 50 When the content is within the above range, good operability can be maintained and, for example, the energy density of an all-solid-state lithium-ion battery can be further improved.
[0101] (Annealing process)
[0102] In the method for producing an inorganic material of the present embodiment, from the viewpoint of further improving the lithium ion conductivity of the obtained inorganic material, an annealing process for crystallizing at least a portion of the inorganic material may be performed. The annealing process may be performed before process (B) or after process (B), but is preferably performed after process (B) from the viewpoint of being able to obtain a further smaller average particle size.
[0103] By performing the annealing step, at least a portion of the glass-state inorganic material is crystallized, and the inorganic material can be made into a glass-ceramic state. In this way, for example, an inorganic material having further excellent lithium ion conductivity can be obtained.
[0104] The temperature when heating the inorganic material in a glassy state is not particularly limited as long as it is a temperature at which crystallization can be fully carried out. For example, from the viewpoint of effectively carrying out crystallization while suppressing thermal decomposition of the inorganic material, it is preferably in the range of 220°C to 500°C, preferably in the range of 250°C to 400°C, more preferably in the range of 260°C to 350°C, and even more preferably in the range of 270°C to 350°C.
[0105] As long as the time that inorganic material is heated is the time that inorganic material of desired glass ceramic state can be obtained, there is no particular limitation, for example, in the scope of more than 1 minute and below 24 hours, preferably in the scope of more than 0.5 hour and below 8 hours, more preferably in the scope of more than 1 hour and within 3 hours. There is no particular limitation to heating method, for example, the method using firing furnace can be enumerated. It should be noted that, in order to make the characteristic of inorganic material most suitable, conditions such as temperature, time when this heating can be appropriately adjusted.
[0106] In addition, the inorganic material is preferably heated in, for example, an inert gas atmosphere, thereby preventing the inorganic material from being degraded (eg, oxidized).
[0107] As the inert gas used when heating the inorganic material, for example, argon, helium, nitrogen, etc. can be cited. In order to avoid impurities from being mixed into the product, the higher the purity of these inert gases, the better. In addition, in order to avoid contact with moisture, the dew point is preferably below -30°C, more preferably below -50°C, and particularly preferably below -60°C. As a method for introducing the inert gas into the mixed system, there is no particular limitation as long as the mixed system is filled with an inert gas environment. Examples include a method of purging the inert gas and a method of continuously introducing a specified amount of inert gas.
[0108] In the annealing process, it is preferred to perform annealing until a diffraction peak different from that of the inorganic material in the glass state is observed in the spectrum obtained by X-ray diffraction using CuKα rays as a radiation source. Here, it is considered that the observation of a diffraction peak different from that of the inorganic material in the glass state means that at least a portion of the inorganic material in the glass state is crystallized, thereby becoming a glass ceramic state.
[0109] Furthermore, generally, when performing X-ray diffraction analysis using CuKα rays as a radiation source, if a new diffraction peak different from the diffraction peak of an inorganic material in a glass state is generated, it can be determined that the inorganic material has been annealed to become a glass ceramic state.
[0110] (Process (C))
[0111] Figure 2 This is a schematic plan view of the separation device 30 used in the step (C) of the method for producing an inorganic material according to the first embodiment. Figure 3 is along Figure 2 Schematic cross-sectional view of AA′.
[0112] exist Figure 2 and Figure 3In the figure, the first direction X is a direction parallel to the horizontal direction orthogonal to the vertical direction. The second direction Y is a direction parallel to the horizontal direction and is orthogonal to the first direction X. The third direction Z is a direction parallel to the vertical direction. The arrow representing the first direction X, the second direction Y or the third direction Z indicates that the direction from the base end of the arrow toward the front end is the positive direction of the direction represented by the arrow, and the direction from the front end of the arrow toward the base end is the negative direction of the direction represented by the arrow. The white circle with a black dot representing the first direction X, the second direction Y or the third direction Z indicates that the direction from the inner side of the paper to the outer side of the paper is the positive direction of the direction represented by the arrow, and the direction from the outer side of the paper to the inner side is the negative direction of the direction represented by the arrow. The positive direction of the third direction Z is the upward direction of the vertical direction, and the negative direction of the third direction Z is the downward direction of the vertical direction. The same is true for the first direction X, the second direction Y and the third direction Z in the figures described later.
[0113] The separation device 30 includes a container 310 and a stirring unit 320. The container 310 contains at least one crushing ball ( Figure 2 as well as Figure 3 The second inorganic material is attached to the grinding balls after step (B). The stirring part 320 is provided in the container 310. The stirring part 320 has a shaft part 322 and a plurality of blade parts 324.
[0114] The container 310 is in the shape of a cylinder with an open upper end and a closed lower end. The side portion of the container 310 is a mesh member 312. The mesh member 312 is made of metal such as SUS304. The mesh member 312 can be provided on the entire side portion of the container 310, or only on a part of the side portion of the container 310. The volume of the container 310 is not particularly limited, and is, for example, 0.5L or more and 2.0L or less.
[0115] The shaft portion 322 extends parallel to the third direction Z. A plurality of blade portions 324 are mounted on the side of the shaft portion 322. When viewed from the third direction Z, a plurality of blade portions 324, specifically four plate-shaped blade portions 324, are arranged at equal intervals along the circumferential direction of the shaft portion 322. The number and arrangement of the blade portions 324 mounted on the shaft portion 322 are not limited to the example of the present embodiment. By rotating the shaft portion 322, the plurality of blade portions 324 rotate to stir the crushing balls. Similar to step (B), at least two crushing balls with different diameters can also be stirred in the container 310. The rotation speed of the shaft portion 322 can be set, for example, to be greater than 1500 rpm and less than 3000 rpm. By stirring the crushing balls, the crushing balls collide with the mesh member 312. In the manner described above, in the present embodiment, the crushing balls are stirred inside an area at least partially surrounded by the mesh member 312.
[0116] According to this embodiment, for example, compared with the case where the pulverizing balls are sieved, the pulverizing balls can be brought into contact with the mesh member 312 with a stronger force. Therefore, compared with the case where the pulverizing balls are sieved, the inorganic material adhering to the pulverizing balls can be separated from the pulverizing balls in a shorter time.
[0117] Figure 4 This is an enlarged schematic diagram of a part of the mesh member 312 of the first embodiment.
[0118] A plurality of holes 314 are arranged in a grid shape on the mesh member 312, for example, by expanded metal. When viewed in the depth direction of the hole 314, the hole 314 is polygonal, specifically, a rhombus shape. That is, the hole 314 is a shape with corners. In this case, compared with the case where the hole 314 is a shape without corners such as a circle or an ellipse, the crushing ball collides with the corner of the hole 314, making it easier to scrape off the inorganic material from the crushing ball. It should be noted that the corner may not be strictly pointed, but may also have roundness. In addition, the hole 314 may also be a polygon different from the rhombus shape, such as a triangle, a quadrangle, a pentagon, a hexagon, an octagon, or other polygonal shapes. Alternatively, the hole 314 may also be a shape without corners such as a circle or an ellipse.
[0119] The vertical width WV of the hole 314 is not particularly limited as long as the crushing ball does not pass through the hole 314, and can be set to, for example, 1.0 mm or more and 3.0 mm or less. The horizontal width WH of the hole 314 is not particularly limited as long as the crushing ball does not pass through the hole 314, and can be set to, for example, 1.0 mm or more and 3.0 mm or less. In addition, the thickness T of the mesh member 312 is not particularly limited, and can be set to, for example, 0.50 mm or more and 1.00 mm or less. The size of the hole 314 can be different depending on the position of the container 310, for example, the size of the hole 314 in the upper part of the container 310 can be different from the size of the hole 314 in the lower part of the container 310.
[0120] At least the surface of the mesh member 312 can be made of a material having a higher Vickers hardness than the material constituting the crushing ball. For example, when the crushing ball is composed of ZrO2, the mesh member 312 can be made of stainless steel such as SUS304 coated with diamond-like carbon (DLC). Assuming that the Vickers hardness of the surface of the mesh member 312 is lower than the Vickers hardness of the crushing ball, the crushing ball collides with the mesh member 312, causing a portion of the surface of the mesh member 312 to be ground, and impurities may enter the second inorganic material. In contrast, when the Vickers hardness of the surface of the mesh member 312 is higher than the Vickers hardness of the crushing ball, it is possible to suppress impurities from mixing into the second inorganic material. It should be noted that the surface of the mesh member 312 can also be made of a material having a lower Vickers hardness than the Vickers hardness of the material constituting the crushing ball.
[0121] (Implementation Method 2)
[0122] Figure 5 It is a schematic plan view of the separation device 30 according to the second embodiment. Figure 6 It is a schematic side view of the separation device 30 according to the second embodiment. Figure 7 is along Figure 5 Schematic cross-sectional view of BB′. Figure 8 It is a schematic enlarged view of a part of the mesh member 312 of Embodiment 2. The separation device 30 of Embodiment 2 is the same as the separation device 30 of Embodiment 1 except for the following points.
[0123] In the present embodiment, when viewed from the third direction Z, the two blade portions 324 are arranged at equal intervals along the circumferential direction of the shaft portion 322. It should be noted that the number and arrangement of the blade portions 324 are not limited to the example of the present embodiment. In addition, the blade portion 324 is rod-shaped. In this case, compared with the case where the blade portion 324 is plate-shaped, it is possible to suppress impurities caused by the wear of the blade portion 324 from mixing into the second inorganic material.
[0124] The plurality of holes 314 are arranged in a herringbone pattern on the mesh member 312, for example, by punching metal. The holes 314 are elongated when viewed in the depth direction of the holes 314. In this case, compared with a case where the holes 314 are not elongated, such as circles, the crushing balls collide with the ends of the holes in the longitudinal direction, and the inorganic material can be scraped off more easily from the crushing balls.
[0125] The length LL of the hole 314 in the longitudinal direction is not particularly limited as long as the crushing ball does not pass through the hole 314, and can be set to, for example, 5.0 mm or more and 15.0 mm or less. The length LS of the hole 314 in the width direction is not particularly limited as long as the crushing ball does not pass through the hole 314, and can be set to, for example, 0.50 mm or more and 1.50 mm or less. In addition, the thickness T of the mesh member 312 is not particularly limited, and can be set to, for example, 0.50 mm or more and 1.50 mm or less.
[0126] The mesh member 312 has at least one protrusion shape 316 protruding toward the area surrounded by the mesh member 312. The protrusion height of the protrusion shape 316 is, for example, 0.50 mm or more and 1.50 mm or less. In the present embodiment, a plurality of protrusion shapes 316 are provided on the inner side of the container 310. It should be noted that the number of protrusion shapes 316 provided on the container 310 may also be only one. In the present embodiment, a group of protrusion shapes 316 arranged in the third direction Z and another group of protrusion shapes 316 arranged in the third direction Z differently from the above group of protrusion shapes 316 are arranged alternately in the horizontal direction. It should be noted that the layout of the plurality of protrusion shapes 316 is not limited to the example of the present embodiment. In the case where the protrusion shape 316 is provided, the movement of the crushing balls stirred in the container 310 can be complicated compared to the case where the protrusion shape 316 is not provided, and the second inorganic material can be separated more easily from the crushing balls. It should be noted that the protrusion shape 316 may not be provided.
[0127] (Variation Example)
[0128] Fig. 9 Schematic diagram of a separation device 30 according to a modified example. The separation device 30 according to the modified example is the same as the separation device 30 according to the first or second embodiment except for the following points.
[0129] The separation device 30 has a blower 330 that blows crushing balls (not shown) toward the mesh member 312. The blower 330 is, for example, a shot blast machine. In this modification, the crushing balls can also be brought into contact with the mesh member 312 with a stronger force than when the crushing balls are sieved. Therefore, compared with the case where the crushing balls are oscillated horizontally on the sieve, the inorganic material attached to the crushing balls can be separated from the crushing balls in a shorter time.
[0130] As mentioned above, although embodiment and modification of this invention were demonstrated, these are an example of this invention, and various structures other than the above-mentioned can also be employ|adopted.
[0131] It should be noted that the present invention is not limited to the aforementioned embodiments or variations, and variations and improvements within the scope of the purpose of the present invention are also included in the present invention. For example, in embodiments 1 and 2 and variations, process (C) includes a process of causing the crushing balls to collide with the mesh member. However, process (C) may include a process of sieving the crushing balls instead of causing the crushing balls to collide with the mesh member. In this case, the second inorganic material attached to the crushing balls can also be recovered.
[0132] Example
[0133] Hereinafter, the present invention will be described with reference to Examples and Comparative Examples, but the present invention is not limited thereto.
[0134] [1] Measurement method
[0135] First, the measurement methods in the following Examples and Comparative Examples are described.
[0136] (1) Particle size distribution
[0137] The particle size distribution of the sulfide-based inorganic solid electrolyte materials obtained in the examples and comparative examples was measured by laser diffraction using a laser diffraction scattering particle size distribution measuring apparatus (Mastersizer 3000 manufactured by Malvern). Based on the measurement results, the particle size at 50% accumulation in the weight-based cumulative distribution of the sulfide-based inorganic solid electrolyte material (d 50 , average particle size).
[0138] (2) Confirmation of condensates
[0139] After the sulfide-based inorganic solid electrolyte material in a glassy state is pulverized using a ball mill for a predetermined period of time, the state inside the ball mill is observed to examine the presence or absence of aggregates.
[0140] (3) Confirmation of scanning electron microscope (SEM) images
[0141] The sulfide-based inorganic solid electrolyte material separated from the pulverized balls was observed by SEM to examine the presence or absence of aggregates.
[0142] <Example 1>
[0143] (1) Preparation of the first inorganic material
[0144] A glassy sulfide-based inorganic solid electrolyte material as the first inorganic material was prepared according to the following procedure.
[0145] As raw materials, Li2S (produced by Furukawa Metals Co., Ltd., purity 99.9%), P2S5 (produced by Kanto Chemical Co., Ltd.), and Li3N (produced by Furukawa Metals Co., Ltd.) were used.
[0146] First, a raw inorganic composition was prepared by mixing Li2S powder, P2S5 powder, and Li3N powder (Li2S:P2S5:Li3N=71.1:23.7:5.3 (mol %)) in a glove box.
[0147] Then, the raw material inorganic composition and 6200 g of ZrO2 balls having a diameter of 25 mm were placed in an alumina cylindrical container (internal volume 5 L) in the glove box, and the cylindrical container was sealed.
[0148] Next, a cylindrical container made of aluminum oxide was installed in a ball mill, and a mechanochemical treatment was performed at 100 rpm for 500 hours to vitrify the raw inorganic composition. Next, the obtained inorganic material was passed through a sieve with a mesh size of 20 μm to obtain a glassy sulfide-based inorganic solid electrolyte material (Li 10 P3S 12 ). The average particle size d of the glassy sulfide-based inorganic solid electrolyte material as the first inorganic material 50 4.5 μm, d 10 2.0 μm, d 90 is 10μm.
[0149] (2) Preparation of the Second Inorganic Material
[0150] Next, 300 g of a glassy sulfide-based inorganic solid electrolyte material as the first inorganic material, 6200 g of ZrO2 balls with a diameter of 2.0 mm, 1200 g of ZrO2 balls with a diameter of 1.0 mm, and 1200 g of ZrO2 balls with a diameter of 5.0 mm were placed inside an alumina cylindrical container (internal volume 5 L) in the glove box, and the cylindrical container was sealed. Next, the alumina cylindrical container was installed in a ball mill and pulverized for 50 hours to micronize the first inorganic material to obtain a second inorganic material. Here, as Figure 1 As shown in (a), the cylindrical container 100 is placed on a rotating table 101, rotated at 100 rpm with the cylindrical axis X as the axis, and the cylindrical container 100 is swung up and down, so that the two ends of the cylindrical container 100 reciprocate in a direction perpendicular to the direction of the cylindrical axis X with a swing frequency of 3 cpm.
[0151] The average particle size d of the glassy sulfide-based inorganic solid electrolyte material obtained as the second inorganic material is 50 2.0 μm, d 10 1.0 μm, d 90 is 3.0μm.
[0152] In addition, in the glassy state of sulfide-based inorganic solid electrolyte materials (Li 10 P3S 12 ) No aggregates of the sulfide-based inorganic solid electrolyte material in a glassy state were observed inside the ball mill after the pulverization was completed.
[0153] (3) Separation of the second inorganic material
[0154] As the separation device, a rice polishing machine RSF-A100 manufactured by Tiger Thermos Co., Ltd. was prepared. The rice polishing machine of Example 1 has the same configuration as the separation device 30 of Embodiment 1, and includes a container and a stirring unit.
[0155] The container is a cylindrical shape with an open upper end and a closed lower end and an internal volume of 1.0 L. Figure 4 Similarly to the example shown, the side portion of the container is a mesh member of SUS304 with a thickness of 0.8 mm, and a plurality of diamond-shaped holes with a vertical width of 2.9 mm and a horizontal width of 2.1 mm are arranged in a lattice at the bottom of the container by expanded metal, and a vertical width of 2.8 mm and a horizontal width of 2.5 mm are arranged at the top of the container.
[0156] and Figure 2 and Figure 3 In the illustrated example, the stirring portion includes a shaft portion and four plate-shaped blade portions arranged at equal intervals in the circumferential direction of the shaft portion.
[0157] 500 g of ZrO2 balls with a diameter of 2.0 mm, a diameter of 1.0 mm, and a diameter of 5.0 mm after the preparation of the second inorganic material (2) are placed in the container of a rice polishing machine, and the shaft is rotated at 2000 rpm to stir the ZrO2 balls for 30 seconds. Based on the comparison of the total mass of the ZrO2 balls before the preparation of the second inorganic material (2) and the total mass of the ZrO2 balls after the preparation of the second inorganic material (2), it is estimated that for every 1 g of ZrO2 balls, 0.106 g of the second inorganic material is attached to the ZrO2 balls. After stirring, 52.7 g of the second inorganic material separated from the ZrO2 balls is recovered. That is, the recovery rate of the second inorganic material is 99.4%.
[0158] Fig.10 This is a diagram showing a SEM image of the second inorganic material separated from the pulverizing balls in Example 1. Fig.10 The image in the upper part is a 5000-fold magnification image. Fig.10 The image in the lower part is a 1000-fold magnification image. Fig.10 As shown, almost no condensate is observed.
[0159] <Example 2>
[0160] (1) Preparation of the first inorganic material and (2) Preparation of the second inorganic material
[0161] The (1) preparation of the first inorganic material and (2) preparation of the second inorganic material in Example 2 are the same as the (1) preparation of the first inorganic material and (2) preparation of the second inorganic material in Example 1.
[0162] (3) Separation of the second inorganic material
[0163] As the separation device, a rice polishing machine RCI-B5-W manufactured by Japan Iris Ohyama Co., Ltd. was prepared. The rice polishing machine of Example 2 has the same structure as the separation device 30 of Embodiment 2, and includes a container and a stirring unit.
[0164] The container is a cylindrical shape with an open upper end and a closed lower end and an internal volume of 1.0 L. Figure 8 Similarly to the example shown, the side of the container is a mesh member of SUS304 with a thickness of 0.8 mm, and a plurality of long holes with a length of about 9 mm in the longitudinal direction and about 1 mm in the width direction are arranged in a herringbone pattern by punching metal. Figures 5 to 8 In the example shown, three protrusions arranged in the vertical direction and four protrusions arranged in the vertical direction differently from the three protrusions are arranged alternately in the horizontal direction on the inner wall of the container. The protrusion height is about 1 mm.
[0165] and Figure 5 to Figure 7 In the illustrated example, the stirring portion includes a shaft portion and two bar-shaped blade portions arranged at equal intervals in the circumferential direction of the shaft portion.
[0166] 400 g of ZrO2 balls with a diameter of 2.0 mm, a diameter of 1.0 mm, and a diameter of 5.0 mm after the preparation of the second inorganic material (2) are placed in the container of a rice polishing machine, and the shaft is rotated at 2000 rpm to stir the ZrO2 balls for 30 seconds. Based on the comparison of the total mass of the ZrO2 balls before the preparation of the second inorganic material (2) and the total mass of the ZrO2 balls after the preparation of the second inorganic material (2), it is estimated that for every 1 g of ZrO2 balls, 0.106 g of the second inorganic material is attached to the ZrO2 balls. After stirring, 42.2 g of the second inorganic material separated from the ZrO2 balls is recovered. That is, the recovery rate of the second inorganic material is 99.5%.
[0167] Fig.11 This is a diagram showing a SEM image of the second inorganic material separated from the pulverizing balls in Example 2. Fig.11 The image in the upper part is a 5000-fold magnification image. Fig.11 The image in the lower part is a 1000-fold magnification image. Fig.11 As shown in the figure, almost no agglomerates were observed. In addition, the agglomerates observed in Example 2 were less than those observed in Example 1.
[0168] <Comparative Example>
[0169] like Figure 1 As shown in (b), a glassy sulfide-based inorganic solid electrolyte material is prepared in the same manner as in Example except that the cylindrical container 100 is not swung up and down (that is, step (B2) is not performed).
[0170] The average particle size d of the glassy sulfide-based inorganic solid electrolyte material obtained as the second inorganic material is 50 9.8 μm, d10 4.0 μm, d 90 It is 14.7μm.
[0171] In addition, in the glassy state of sulfide-based inorganic solid electrolyte materials (Li 10 P3S 12 ) After the pulverization was completed, agglomerates of the sulfide-based inorganic solid electrolyte material in a glassy state were observed inside the ball mill.
[0172] By comparing Examples 1 and 2 with the comparative example, it can be understood that the manufacturing method of the example in which step (B2) is performed can suppress the generation of agglomerates and obtain an inorganic material with a smaller average particle size. In addition, when step (B2) is performed, it can be said that the second inorganic material can be attached to the crushing ball compared to the inner wall of the cylindrical container compared to the case where step (B2) is not performed. Furthermore, by performing step (C), it can be said that the second inorganic material attached to the crushing ball can be recovered.
[0173] This application is based on Japanese Patent Application No. 2020-173894 filed on October 15, 2020 and claims the priority of the Japanese Patent Application. The entire contents of the Japanese Patent Application are incorporated herein into this application.
[0174] Description of Reference Numerals
[0175] 30 Separation device
[0176] 100 Cylindrical Container
[0177] 101 Rotating Table
[0178] 310 Container
[0179] 312 mesh components
[0180] 314 holes
[0181] 316 Protrusion shape
[0182] 320 Mixing Unit
[0183] 322 Shaft
[0184] 324 Blade
[0185] X Cylinder axis.
Claims
1. A method for producing an inorganic material, wherein: include: A step (A) of preparing a first inorganic material as a raw material; (B) a step of obtaining a second inorganic material by pulverizing the first inorganic material using a ball mill composed of a cylindrical container and pulverizing balls to micronize the first inorganic material; as well as a step (C) of separating the second inorganic material from the crushing balls to which the second inorganic material is attached, The step (B) comprises: after placing the first inorganic material and the pulverizing balls in the cylindrical container, a step (B1) of rotating the cylindrical container about a cylindrical axis; and a step (B2) of moving the cylindrical container so that the first inorganic material moves along the cylindrical axis. In the step (B2), at least one end of the cylindrical container is reciprocated in a direction perpendicular to the cylindrical axis direction, thereby moving the first inorganic material in the cylindrical axis direction.
2. The method for producing an inorganic material according to claim 1, wherein: The step (C) includes a step of causing the pulverizing balls to collide with a mesh member.
3. The method for producing an inorganic material according to claim 2, wherein: The step of causing the pulverizing balls to collide with the mesh member includes the step of stirring the pulverizing balls inside a region at least partially surrounded by the mesh member.
4. The method for producing an inorganic material according to claim 3, wherein: At least one hole formed in the mesh member is polygonal or strip-shaped.
5. The method for producing an inorganic material according to claim 3, wherein: The step of stirring the pulverizing balls includes the step of stirring at least two types of pulverizing balls having different diameters in the region surrounded by the mesh member.
6. The method for producing an inorganic material according to claim 3, wherein: At least the surface of the mesh member is composed of a material having a higher Vickers hardness than the Vickers hardness of a material constituting the pulverizing balls.
7. The method for producing an inorganic material according to any one of claims 1 to 4, wherein: In the step (B), the first inorganic material is pulverized in a dry state.
8. The method for producing an inorganic material according to any one of claims 1 to 4, wherein: The first inorganic material and the second inorganic material are inorganic solid electrolyte materials, positive electrode active materials or negative electrode active materials.
9. The method for producing an inorganic material according to any one of claims 1 to 4, wherein: The first inorganic material and the second inorganic material include a sulfide-based inorganic solid electrolyte material.
10. The method for producing an inorganic material according to any one of claims 1 to 4, wherein The grinding balls in step (B) include two or more types of grinding balls having different diameters.
11. A method for producing an inorganic material, wherein: include: A step (A) of preparing a first inorganic material as a raw material; (B) a step of obtaining a second inorganic material by pulverizing the first inorganic material using a ball mill composed of a cylindrical container and pulverizing balls to micronize the first inorganic material; as well as a step (C) of separating the second inorganic material from the crushing balls to which the second inorganic material is attached, The step (B) comprises: after placing the first inorganic material and the pulverizing balls in the cylindrical container, a step (B1) of rotating the cylindrical container about a cylindrical axis; and a step (B2) of moving the cylindrical container so that the first inorganic material moves along the cylindrical axis. The step (C) includes causing the pulverizing balls to collide with a mesh member. The step of causing the pulverizing balls to collide with the mesh member includes the step of stirring the pulverizing balls in a region at least partially surrounded by the mesh member. The mesh member has at least one protrusion shape protruding toward the area surrounded by the mesh member, The mesh member is disposed on a side surface of the cylindrical container.
12. The method for producing an inorganic material according to claim 11, wherein: The step of stirring the pulverizing balls includes the step of stirring at least two types of pulverizing balls having different diameters in the region surrounded by the mesh member.
13. The method for producing an inorganic material according to claim 11, wherein: At least the surface of the mesh member is composed of a material having a higher Vickers hardness than the Vickers hardness of a material constituting the pulverizing balls.
14. The method for producing an inorganic material according to claim 11, wherein: In the step (B), the first inorganic material is pulverized in a dry state.
15. The method for producing an inorganic material according to claim 11, wherein: In the step (B2), the first inorganic material is moved along the cylindrical axis direction by reciprocating the cylindrical container along the cylindrical axis direction and / or reciprocating at least one end of the cylindrical container in a direction perpendicular to the cylindrical axis direction.
16. The method for producing an inorganic material according to any one of claims 11 to 15, wherein: The first inorganic material and the second inorganic material are inorganic solid electrolyte materials, positive electrode active materials or negative electrode active materials.
17. The method for producing an inorganic material according to any one of claims 11 to 15, wherein: The first inorganic material and the second inorganic material include a sulfide-based inorganic solid electrolyte material.
18. The method for producing an inorganic material according to any one of claims 11 to 15, wherein: The grinding balls in step (B) include two or more types of grinding balls having different diameters.
19. A method for producing an inorganic material, wherein: include: A step (A) of preparing a first inorganic material as a raw material; (B) a step of obtaining a second inorganic material by pulverizing the first inorganic material using a ball mill composed of a cylindrical container and pulverizing balls to micronize the first inorganic material; as well as a step (C) of separating the second inorganic material from the crushing balls to which the second inorganic material is attached, The step (B) comprises: after placing the first inorganic material and the pulverizing balls in the cylindrical container, a step (B1) of rotating the cylindrical container about a cylindrical axis; and a step (B2) of moving the cylindrical container so that the first inorganic material moves along the cylindrical axis. The step (C) includes causing the pulverizing balls to collide with a mesh member. The step of causing the pulverizing balls to collide with the net-like member includes the step of blowing the pulverizing balls toward the net-like member.
20. The method for producing an inorganic material according to claim 19, wherein: At least the surface of the mesh member is composed of a material having a higher Vickers hardness than the Vickers hardness of a material constituting the pulverizing balls.
21. The method for producing an inorganic material according to claim 19, wherein: In the step (B), the first inorganic material is pulverized in a dry state.
22. The method for producing an inorganic material according to claim 19, wherein: In the step (B2), the first inorganic material is moved along the cylindrical axis direction by reciprocating the cylindrical container along the cylindrical axis direction and / or reciprocating at least one end of the cylindrical container in a direction perpendicular to the cylindrical axis direction.
23. The method for producing an inorganic material according to claim 19, wherein: The first inorganic material and the second inorganic material are inorganic solid electrolyte materials, positive electrode active materials or negative electrode active materials.
24. The method for producing an inorganic material according to claim 19, wherein: The first inorganic material and the second inorganic material include a sulfide-based inorganic solid electrolyte material.
25. The method for producing an inorganic material according to claim 24, wherein: The sulfide-based inorganic solid electrolyte material has lithium ion conductivity and contains Li, P, and S as constituent elements.
26. The method for producing an inorganic material according to claim 25, wherein: In the sulfide-based inorganic solid electrolyte material, a molar ratio Li / P of the Li content to the P content is 1.0 to 10.0, and a molar ratio S / P of the S content to the P content is 1.0 to 10.
0.
27. The method for producing an inorganic material according to claim 24, wherein: The sulfide-based inorganic solid electrolyte material as the first inorganic material is in a glass state.
28. The method for producing an inorganic material according to any one of claims 19 to 27, wherein: The grinding balls in step (B) include two or more types of grinding balls having different diameters.
29. The method for producing an inorganic material according to claim 28, wherein: The pulverizing balls include first pulverizing balls having a diameter in a range of 1.5 mm to 2.5 mm, and second pulverizing balls having a diameter in a range of 0.2 mm to less than 1.5 mm.
30. The method for producing an inorganic material according to claim 29, wherein: The pulverizing balls further include third pulverizing balls having a diameter in a range of greater than 2.5 mm and less than or equal to 10.0 mm.
Citation Information
Patent Citations
Sulfide solid electrolytic material, battery, and method for manufacturing sulfide solid electrolytic material
JP2016027545A
Joint connector
JP2020173894A
Cylinder screen for ball mill
CN207769936U
Ball mill
JP2004216373A
Pulverizer
JP2007190480A